2009
DOI: 10.3174/ajnr.a1940
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Sclerotherapy for Facial Venous Malformations: Subjective Clinical and Objective MR Imaging Follow-Up Results

Abstract: BACKGROUND AND PURPOSE:Venous malformations are the most common of all vascular anomalies, 40% of which are found in the head and neck. We discuss results of percutaneous sclerotherapy using bleomycin for facial VMs by using subjective clinical assessment and objective changes on MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 14 publications
8
62
1
1
Order By: Relevance
“…This has been shown by Ionescu et al 16 , who found no detectable bleomycin in blood samples taken from 4 pediatric patients between 10 minutes and 24 hours after sclerotherapy for hemangioma treatment. In addition, both the per session and cumulative doses of bleomycin used for sclerotherapy (<15 and <250 U, respectively [4][5][6]15,18 ) are well below the systemic dose of 450 mg recognized in the cancer literature to be associated with an increased risk of pulmonary fibrosis. 17 Recognizing the utility of bleomycin in the treatment of vascular anomalies, Muir et al 4 treated 95 patients with hemangiomas and congenital vascular malformations, 31 of which were VMs.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown by Ionescu et al 16 , who found no detectable bleomycin in blood samples taken from 4 pediatric patients between 10 minutes and 24 hours after sclerotherapy for hemangioma treatment. In addition, both the per session and cumulative doses of bleomycin used for sclerotherapy (<15 and <250 U, respectively [4][5][6]15,18 ) are well below the systemic dose of 450 mg recognized in the cancer literature to be associated with an increased risk of pulmonary fibrosis. 17 Recognizing the utility of bleomycin in the treatment of vascular anomalies, Muir et al 4 treated 95 patients with hemangiomas and congenital vascular malformations, 31 of which were VMs.…”
Section: Discussionmentioning
confidence: 99%
“…In a case study of 37 patient of head and neck vascular malformation (VM), using pre and post sclerotherapy MR imaging, Spence et al [20] reported that Percutaneous sclerotherapy by using bleomycin is a safe technique to objectively decrease size and subjectively alleviate symptoms of facial VMs. Subjective clinical improvement is not always associated with visual size reduction on MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Various chemical agents have been used like ethanol, polidocanol and Bleomycin [17,18]. Percutaneous USG guided intralesional Bleomycin infiltration had a remarkable success rate for treatment of facial hemangiomas as minimal size reduction or partial fibrosis of the lesion may be enough to achieve subjective clinical improvement [18].…”
Section: Discussionmentioning
confidence: 99%